1983
DOI: 10.1021/ic00143a017
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of axial ligand field strength and zero-field splittings in the carbon-13 NMR spectra of five- and six-coordinate high-spin iron(III) porphyrin complexes

Abstract: Carbon-13 NMR spectra have been recorded for complexes of high-spin iron(III) porphyrins in which the axial anionic ligand has been varied. The (Me2SO)2 complexes of high-spin iron(III) tetraphenylporphyrins ((TPP)Fe111) and natural-derivative porphyrins have also been examined. Replacement of a single anionic ligand with two solvent ligands induces striking changes in carbon-13 NMR spectra, with changes in the phenyl ortho-carbon and meso-carbon signals of (TPP)Fe111 on the order of several hundred ppm. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Every chemical bond has a bond critical point at which the first derivative of the charge density, ρ (r), is zero. 13,14 The ρ(r) topology is described by a real, symmetric, second-rank Hessian-of-ρ(r) tensor, and the tensor trace is related to the bond interaction energy by a local expression of the virial theorem: (5) where ∇ 2 ρ(r) is the Laplacian of ρ(r) and G(r) and V(r) are electronic kinetic and electronic potential energy densities, respectively. Negative and positive ∇ 2 ρ(r) values are associated with shared-electron (covalent) interactions and closed-shell (electrostatic) interactions, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every chemical bond has a bond critical point at which the first derivative of the charge density, ρ (r), is zero. 13,14 The ρ(r) topology is described by a real, symmetric, second-rank Hessian-of-ρ(r) tensor, and the tensor trace is related to the bond interaction energy by a local expression of the virial theorem: (5) where ∇ 2 ρ(r) is the Laplacian of ρ(r) and G(r) and V(r) are electronic kinetic and electronic potential energy densities, respectively. Negative and positive ∇ 2 ρ(r) values are associated with shared-electron (covalent) interactions and closed-shell (electrostatic) interactions, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…3,4 For example, the iron centers in paramagnetic proteins (and model systems) have a >5000 ppm range of 13 C NMR shifts 5,6 and are well-correlated with electronic structure. 7 While 1 H NMR shifts are typically smaller, recent studies on several blue copper proteins (BCPs), amicyanin (Am), 8 azurin (Az), 9 plastocyanin (Pc), 10 pseudoazurin (Pa), 11 stellacyanin (St), 9 and rusticyanin (Rc), 11 revealed that the Cys-C β H 2 shifts are in the range of ~240-850 ppm, 9-11 since they are only three bonds removed from the paramagnetic (Cu II ) center.…”
Section: Introductionmentioning
confidence: 99%
“…12 Goff and co-workers have reported correlations of axial ligand field strength and zero-field splittings in the C-13 NMR spectra of 5-and 6-coordinate high-spin Fe(III) porphyrin complexes. 13 Ohya and Sato conducted a comparative study of Mossbauer spectra of -fold symmetry, their crystals are in the monoclinic system. Thus, the rhombic parameter E in eq 1 is required to explain ZFS properties of their crystalline samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[7][8][9][10] For planar porphyrin ligands, such as high-spin FeTPPCl (or FeOEPCl), the meso-C signal appears at a downfield position of 500 ppm (or 380 ppm), and 368 ppm (or 246 ppm) for the admixed (5/2, 3/2) FeTPPClO 4 (or FeOEPClO 4 ), respectively (see Table 1; TPP = dianion of 5,10,15,20-tetraphenylporphyrin and OEP = dianion of 2,3,7,8,12,13,17,18-octaethylporphyrin). [11,12] These downfield shifts at the meso-C atoms have been attributed by Cheng et al to interactions between the iron(III) d z 2 and the porphyrin a 2u orbitals. [13] However, for saddled porphyrin ligands, considering the main skeleton of the macrocycle, the five-coordinate saddleshaped Fe(OETPP)Cl has a local C 2v symmetry, which is lower than the C 4v symmetry of five-coordinate planar iron(III) porphyrin complexes.…”
Section: In Memory Of Ru-jen Chengmentioning
confidence: 83%
“…Fe(TPP)X [7,11,12,14] porphyrin complexes in similar spin states so far, but this change has been postulated because of the difference in the geometric structures. [7] In this study, we employed density functional theory (DFT) calculations to correlate the Fe-porphyrin bonding interactions with calculated spin populations, including the total spin, the localized p spin, and the Fermi contact spin densities on the porphyrin macrocycle to elucidate these unexpected NMR data.…”
Section: In Memory Of Ru-jen Chengmentioning
confidence: 99%